The Hostages of History? A victimological outline of Slovenia in the period between 1941 and 1945 - Dežman, Jože (Inštitut za novejšo zgodovino, 1996)
According to the existing data, the Second World War in Slovenia claimed between 65,000 and 75,000 victims or 4 to 4.5 percent of the population which, in 1941, counted aro\ind 1,600,000. As a consequence of repression by the opponents of the partisan movement, between 40,000 and 50,000 partisans, their sympathizers and civilians, or 2.5 to 3.1 percent of the population, died. The forced mobilization of Slovenians into the German army took a further 10,000 lives or 0.6 percent of the population. On the side of the Slovenian opponents of the partisan movement there were over 15,000 victims or 0.9 percent of the population. Those most at risk during the war were the males of conscript age who lived in the rural surroundings of the Ljubljana province and were members of the collaborationist military formations. Po doslej zbranih podatkih je bilo žrtev druge svetovne vojne med Slovenci med 65.000 in 75.000, torej približno med 4,0 in 4.5 odstotka prebivalstva (1941 naj bi bilo Slovencev okoli 1.600.000). Padlih partizanov, pobitih sodelavcev partizanskega gibanja in drugih civilnih žrtev represije nasprotnikov partizanskega gibanja je bilo od 40 do 50.000, kar je od 2.5 do 3.1 odstotka prebivalstva . Posledica okupatorjeve mobilizacije Slovencev v nemško vojsko je bilo več kot 10.000 mrtvih, kar je 0.6 odstotka prebivalstva (sami mobiliziranci ocenjujejo število padlih na 15.000). V vrstah slovenskih nasprotnikov partizanskega gibanja je bilo več kot 15.000 žrtev (0.9 odstotka prebivalstva). Faktorji ogroženosti med vojno so bili predvsem spol, starost, kraj bivanja in vloga v vojni.